2014
DOI: 10.1590/0047-2085000000006
|View full text |Cite
|
Sign up to set email alerts
|

Funções executivas, atividades da vida diária e habilidade motora de idosos com doenças neurodegenerativas

Abstract: Objetivo: Analisar as funções executivas de idosos com doença de Parkinson (DP – com e sem quadro demencial) e doença de Alzheimer (DA), e confrontar os escores dos participantes no que se refere às atividades funcionais da vida diária e à habilidade motora em situações de dupla tarefa. Métodos: Sob um desenho transversal, 54 idosos foram divididos em quatro grupos: G1, composto por 11 sujeitos com DP; G2, formado por 10 sujeitos com demência de Parkinson; G3, composto por 13 participantes com DA; e G4, formad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
24

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
(30 reference statements)
0
10
0
24
Order By: Relevance
“…The disease challenges, especially those related to the loss of motor control, may cause feelings of hopelessness and low self-esteem (Felippe et al, 2014;Queiroz, 2012;Silva et al, 2014;Stern et al, 2012); thus, self-devaluation, self-criticism, and self-disapproval are commonly found Stern et al, 2012). Previous studies have reported an increase in MOR in people with drug abuse problems ) and high Sum V in patients with depression (Villemor-Amaral & Machado, 2011), suggesting the presence of negative thoughts, attitudes, and feelings, evidencing the validity of the ZCS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The disease challenges, especially those related to the loss of motor control, may cause feelings of hopelessness and low self-esteem (Felippe et al, 2014;Queiroz, 2012;Silva et al, 2014;Stern et al, 2012); thus, self-devaluation, self-criticism, and self-disapproval are commonly found Stern et al, 2012). Previous studies have reported an increase in MOR in people with drug abuse problems ) and high Sum V in patients with depression (Villemor-Amaral & Machado, 2011), suggesting the presence of negative thoughts, attitudes, and feelings, evidencing the validity of the ZCS.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests dependent behavior, passivity, reduced self-determination, and less use of authoritarian self-defense in patients with PD, which could have been motivated by difficulties in executing ADL such M. RIEN et al as walking, driving, and personal hygiene (Felippe et al, 2014;Stern et al, 2012), which cause changes in social and family dynamics and require constant care (Bhimani, 2014;Silva et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Todos esses aspectos são fundamentais para manutenção de uma boa funcionalidade e aprendizagem motora, visivelmente comprometidas da DP 14 . O Exergame pode ser uma estratégia terapêutica relevante para ser empregada nestas condições.…”
Section: Tabela 1-unclassified